Length‐weight relationships of 37 freshwater fish species from the Lefini river, middle Congo River basin (Republic of the Congo). (2nd March 2020) - Ibala Zamba, Armel; Vreven, Emmanuel; Mamonekene, Victor; Musschoot, Tobias; Poaty Ngot, Honnest Freedom; Snoeks, Jos
Abstract: The present study reports on length‐weight relationships (LWRs) for 37 of the most abundant fish species in the Lefini River basin, one of the largest right bank tributaries of the Congo River in the Republic of the Congo. The study area comprised 12 stations along 103 km of the river. Each station was sampled during March 2007 to August 2008 following standardized methods utilizing five monofilament gill nets of 10, 12, 15, 20 and 30 mm mesh size. Sample size, lengths, weights, LWRs, 95% confidence intervals of a and b, coefficient of correlation r 2 and growth type are provided for each species. Values of allometric coefficient b of the LWRs (W =  a SL b ) ranged from 2.556 for Synodontis nigriventris to 3.363 for Brycinus poptae . These results represent the first study of length‐weight relationships for fish species in a large affluent of the Congo basin as a whole.